Blockchain-driven logistics provider guaranteed financing strategy considering risk aversion - Yang, Lei; Hou, Qiaoming (Frontiers in Physics, 2025)
IntroductionIn e-commerce supply chains, suppliers generally face funding constraints, and the guaranteed financing provided by logistics providers can effectively improve the capital liquidity of suppliers. Blockchain helps alleviate the information silos in the financing process, strengthen cooperation between enterprises, and enhance the quality of financing. Cooperative and non-cooperative decisions have significant impacts on the formulation of financing strategies, and contract design helps coordinate the interest conflicts between enterprises and optimize financing strategies.MethodsAddressing the financial constraints for suppliers, this study employs game theory analysis to construct a guarantee financing model under blockchain technology where logistics providers offer guarantees to suppliers. It considers the risk-averse of managers and first analyzes the financing equilibrium strategies before and after blockchain in a non-cooperative game setting. Then, under a cooperative game framework, it explores the financing equilibrium strategies in three modes: cooperation between suppliers and logistics providers, cooperation between logistics providers and e-commerce platforms, and cooperation among all three parties. It also compares and analyzes the influence of blockchain on cooperative and non-cooperative game strategies in terms of financing decisions. To coordinate the interest conflicts among various risk-averse members, the study introduces revenue-sharing and cost-sharing to formulate coordination strategies.Results and discussionThrough comparative analysis, it is found that information verification costs can impair the financing gains of suppliers but help ensure the financing gains of logistics providers. Supplier defaults are detrimental to the development of supply chain financing (SCF). The financing gains of suppliers and logistics providers will initially decrease and then increase with the adoption of blockchain, which can better optimize financing strategies once they exceed a certain threshold. A higher risk aversion can harm the financing gains of suppliers and logistics providers but benefit the gains of ecommerce platforms and financial institutions. Compared to non-cooperative modes, cooperative models are more effective in enhancing the financing efficiency, and under cooperative modes, blockchain is more conducive to promoting the improvement of corporate financing gains. The Shapley value can effectively allocate the financing gains among supply chain members, and risk-sharing contracts can increase the financing gains of suppliers and logistics providers. This research aims to provide theoretical references for the financing decisions of supply chain enterprises.